Chromophoric dissolved organic matter export from U.S. rivers. Issue 8 (27th April 2013) - Spencer, Robert G. M.; Aiken, George R.; Dornblaser, Mark M.; Butler, Kenna D.; Holmes, R. Max; Fiske, Greg; Mann, Paul J.; Stubbins, Aron
Abstract : [1] Chromophoric dissolved organic matter (CDOM) fluxes and yields from 15 major U.S. rivers draining an assortment of terrestrial biomes are presented. A robust relationship between CDOM and dissolved organic carbon (DOC) loads is established (e.g., a 350 versus DOC; r 2  = 0.96, p < 0.001). Calculated CDOM yields are also correlated to watershed percent wetland (e.g. a 350 ; r 2  = 0.81, p < 0.001) providing a method for the estimation of CDOM export from ungauged watersheds. A large variation in CDOM yields was found across the rivers. The two rivers in the north‐eastern U.S. (Androscoggin and Penobscot), the Edisto draining into the South Atlantic Bight, and some rivers draining into the Gulf of Mexico (Atchafalaya and Mobile) exhibit the highest CDOM yields, linked to extensive wetlands in these watersheds. If the Edisto CDOM yield is representative of other rivers draining into the South Atlantic Bight, this would result in a CDOM load equivalent to that of the Mississippi from a region of approximately 10% of the Mississippi watershed, indicating the importance of certain regions with respect to the role of terrigenous CDOM in ocean color budgets. Abstract : Key points Multisite CDOM load and DOC load relationship Development of CDOM yields shows important regions for future study First estimate of CDOM flux from major U.S. Rivers